Maternal Mortality and Morbidity in “Hellp” Syndrome : A Study With 70 Patients and Literature Review - Noor, Serajun; Chowdhury, Shahanara; Mahmud, Sayed (Journal of Chittagong Medical College Teachers’ Association, 2012)
The syndrome of haemolysis, elevated liver enzyme and low platelet is considered to be a complication of severe preeclampsia and eclampsia. Study design: This prospective study included 70 patients with : HELLP” syndrome managed in CMCH gynae and obstetric unit 2 from July 2005 to June 2007. “HELLP” syndrome was diagnosed clinically supported by laboratory findings of low platelets, increase AST, ALT, LDH and serum creatinine in patients with severe preeclampsia and eclampsia. Results : Out of 70 patients with “HELLP” 50(71%) patients were antepartum and 20(29%) postpartum. Among antepartum 40(80%) developed “HELLP” less than 36 weeks and 10(20%) between 37-42 weeks of pregnancy. Matrenal death 5(7%) were from complications like pulmonary oedema and acute renal failure. Serious maternal morbidity 56 (80%) included DIC 15(26%), abruption 9(16%), acute renal failure 10(17%), pulmonary Oedema 10(17%) and cerebro-vascular accident 10%). Repeated blood transfusion needed in 14 (25%). There was no difference in laboratory findings of “HELLP” developing before and after delivery. Incidence of acute renal failure and pulmonary oedema were significantly higher in “HELLP” among patients with preeclampsia and postpartum eclampsia rather than “HELLP” in antepartum eclampsia. So it can be concluded that maternal mortality and morbidity is significantly higher when “HELLP” is complicated by pulmonary oedema and acute renal failure. JCMCTA 2011; 22(2): 27-31